Gibellula flava sp. nov. (Cordycipitaceae, Hypocreales), a new pathogen of spider from China - Chen, Ming-Jun; Wang, Ting; Lin, Yan; Huang, Bo (Phytotaxa, 2021)
Gibellula is an exclusively spider-pathogen genus, with most species immediately recognized by their distinctive conidial state, but also including the teleomorphic states of these fungi that were previously included in the rejected genus Torrubiella. Two sexual specimens and an asexual morph specimen were collected from Anhui Province, China, and were recognized as the same species based on molecular evidence. Its asexual morph differs from Gibellula pulchra, to which it is morphologically similar, in having shorter verrucose conidiophores with slightly smaller metulae, phialides and conidia. Its sexual morph is characterized by producing superficial and elongate ellipsoid small perithecia with short asci on a cream-yellow mycelial mat covering the host. Multi-locus (SSU, LSU, TEF, and RPB1) phylogenetic analyses showed that the specimens belong to a strongly supported subclade, and formed a sister subclade with G. pulchra and Gibellula sp. A combination of morphological characteristics and its phylogenetic placement confirmed that these unique specimens are a new species, which is described as Gibellula flava.